Pro-poor capital assistance: A strategic analysis of Baitul Maal wat Tamwil microfinance - Andri Martiana; Zenza Chessara Novada Panena; Nasrul Fahmi Zaki Fuadi (Universitas Negeri Surabaya, 2022)
This paper aims to analyze the potential of the Baitul Maal wat Tamwil (BMT) strategy to empower the lower-middle-class people and analyze the recommended strategy for making economic empowerment through more effective and efficient Islamic microfinance. This research uses the in-depth interview method and SWOT analysis as further analysis. The results indicated that BMT has great potential, especially in human resources development and a clear market share to empower the lower classes of society. However, it is necessary to have an appropriate economic empowerment model following the conditions of the lower classes of society and the need for government roles to support the existence of an Islamic microfinance institution in the form of Baitul Maal wat Tamwiil (BMT). Several economic empowerment strategies have been implemented by Baitul Maal wat Tamwil (BMT). This study adds the existing literature related to Islamic microfinance's role to have the suitable model that efficiently and effectively empowers the poor Indonesian society, especially those who live in Yogyakarta.